Disaster Management in Earthquake-Prone Countries: Lessons from the Public Administration Systems of Japan and the Philippines - Wahyudi Mokobombang; Nurasia Natsir (International Journal of Social Welfare and Family Law, 2026)
This study examines disaster management strategies in earthquake-prone countries, with a comparative focus on Japan and the Philippines as case studies for lessons applicable to public administration systems worldwide. Using a qualitative comparative analysis approach, the research evaluates institutional frameworks, policy instruments, community engagement mechanisms, and intergovernmental coordination systems deployed in both countries. Japan’s highly centralized yet locally adaptive Disaster Management Basic Act framework is contrasted with the Philippines’ decentralized National Disaster Risk Reduction and Management (NDRRM) system. Findings reveal that effective disaster management hinges on five critical pillars: strong legal frameworks, inter-agency coordination, investment in early warning systems, community resilience programs, and post-disaster recovery governance. The study further identifies that public trust, administrative capacity, and fiscal decentralization significantly influence disaster response outcomes. Lessons drawn from both countries offer practical recommendations for developing nations seeking to strengthen their disaster governance architectures. This research contributes to the growing body of knowledge on comparative public administration and disaster risk reduction, underscoring the imperative of integrated, adaptive, and community-centered governance frameworks in seismically active regions.